DEPENDENCY ON FOREST RESOURCE OF THE PEOPLE RESIDING IN KANGKRACHAN NATIONAL PARK - Parhurak, Sirimas; Hoamuangkaew, Wuthipol; Suksard, Santi; Udomchoke, Veerasak (วารสารวนศาสตร์ไทย, 2022)
Objectives of the study were to determine the dependency on forest resource and investigate factors relating to the dependency on forest resource of the villagers residing in Kangkrachan National Park. The designed questionnaires were employed for interviewing 323 respondents. The statistical software package was hired for the data analyses. Correlation analysis was employed for analyzing the relationship between each independent variable and the dependency on each kind of the collected forest product, and with the given significance level of .05 Results of the study indicated that the gender of the most respondents were male (50.2%) and their educational level were at primary school (47.1%). The main occupation of the majority was trading (37.8%). The average size of land holding was 6.35 rais. The average number of household member and labor were 4.37 and 2.62 persons, respectively. The average annual household income was 252,411.10 baht. The most respondents were used to received the information about forest resource conservation (85.1%) and never attended any training course about forest resource conservation (74.9%). The average score of the knowledge about forest resource was 17.16 from the full score of 20. The dependency on forest resource was determined on each kind of 9 kinds of the studied forest products, namely, medicinal plant, wild fruit, bamboo, bamboo shoot, mushroom, edible plant, edible insect, wildlife and firewood. The total value of the collected forest products was 3,740,062.26 baht per annum. Based on the hypothesis test indicated that the main occupation was positively related to the dependency on almost all kinds of the mentioned forest products except firewood. While annual household income was negatively related to the dependency on such kinds of forest products that related to the main occupation. In addition, educational level was negatively related to the dependency on wild fruit, bamboo, bamboo shoot and mushroom. Moreover, the receiving information about forest resource conservation was positively related to the dependency on wild fruit. Finally, number of household number and score of the knowledge about forest resource conservation were negatively related to the dependency on firewood.